Undergraduate students' engagement with systems thinking: results of a survey study - Camelia, Fanny; Ferris, Timothy L. J. (Cranfield University, 2016)
This paper describes the results obtained for the affective engagement of students with systems thinking. In prior work the authors have developed and validated a questionnaire instrument for measuring affective engagement of undergraduate engineering students with systems thinking. This paper presents results obtained when the questionnaire was used with undergraduate students. Two surveys with different versions of the questionnaire, one using positive grammar questions only and the other using a mix of positive and negative constructs, were used to measure the students’ engagement with systems thinking and its relationship with gender, age and work experience. Each questionnaire version was applied to a different sample, the first, 186 participants, completed the positive grammar version, and, the second group of 163 completed the mixed version. The results show that participants in both studies valued systems thinking in each of the three dimensions of the systems thinking construct. Statistical tests confirmed no significant gender differences in either study. Student engagement with the practical dimension of systems thinking was shown to vary, with statistical significance, with groups of age, years of work experience and country of the university.